2014
DOI: 10.1091/mbc.e14-06-1091
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of fluorescent transgene methods for quantitative imaging in human cells

Abstract: Despite widespread use the extent to which different mammalian transgene methods report on the properties of endogenous proteins has not been systematically compared. This study shows that the choice of fluorescence-tagging method fundamentally influences the ability to image the activity of the mitotic kinase Aurora B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 22 publications
2
78
0
Order By: Relevance
“…These experiments reported that Eg5 was enriched at spindle poles relative to microtubules. The discrepancy in the results from the two experimental approaches supports the view that the method of protein tagging can affect protein distribution in cells as reported by others (see Section 4) (Dambournet et al, 2014;Mahen et al, 2014).…”
Section: Tpx2 Is Enriched Relative To Eg5supporting
confidence: 74%
“…These experiments reported that Eg5 was enriched at spindle poles relative to microtubules. The discrepancy in the results from the two experimental approaches supports the view that the method of protein tagging can affect protein distribution in cells as reported by others (see Section 4) (Dambournet et al, 2014;Mahen et al, 2014).…”
Section: Tpx2 Is Enriched Relative To Eg5supporting
confidence: 74%
“…HeLa Kyoto cells are hypotriploid with on average 64 chromosomes, thus during mitosis the cells have on average 64*2 = 128 kinetochores 12 . The cell lines have been generated for this project or previously 16,[26][27][28][29][30][31][32] are listed in Supplementary Table 1 with their providers indicated. Several cell lines were generated within this project as follows: The cell lines expressing PLK1-mEGFP, CEP192-mEGFP and mEGFP-NUP107 were generated using the Zinc finger nuclease (ZFN) pipeline as in 29 .…”
Section: Figure Legendsmentioning
confidence: 99%
“…For these cell lines, both gRNAs ( Supplementary Table 2) and the donor plasmid were designed based on ENSEMBL release 75 and transfected together into HeLa Kyoto cells with jetPrime (Polyplus) according to the manufacturer's instruction. A single clone was selected using our previously developed validation pipeline 6,29 . For 4 out of 20 genome-edited cell lines (BUB1B-EGFP, TPR-mEGFP, mEGFP-NUP107 and CEP192-mEGFP) we detected in the Western blots (anti-GFP, Roche cat#11814460001) a band of the size of free GFP.…”
Section: Figure Legendsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of genomic DNA instead of cDNA vectors in gene therapy has made a way for vital accurate gene expression, as these vectors contain all endogenous control elements in terms of achieving a close to physiologic expression level. The majority of studies have relied on transgenes using cDNA, which actually does not faithfully mimic physiologic gene expression, because it does not contain most of the endogenous cis ‐acting regulatory sequences (50). To date, little effort has gone into detailed analyses of the genomic environments of genetic element‐containing transgenes.…”
Section: Discussionmentioning
confidence: 99%